PERANCANGAN BUSANA EVENING dari BAHAN BATIK BAYAT dengan HIASAN PAYET dan SWAROVSKI - Mrs Jumariah; Putri Isna (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
ABSTRACTThis study aims to find out the results of the design of evening clothing from batik bayat materialwith sequin and Swarovski decorations, which are reviewed in terms of model and colour harmony. Thedevelopment of the fashion world today encourages writers to innovate in evening fashion design inaccordance with fashion trends by using ethnic batik bayat materials combined with brocade and bridalmaterials to add a luxurious impression while to make the fashion beautiful the author provides sequinand Swarovski decorations.The research method uses experimental methods, sensory tests and documentation. The subjectsof her research were two evening dress from bayat batik material combined with brocade and bridalmaterials. The stages of the experiment are designing, taking body size, pattern making, cuttingmaterials, sewing and finishing. Sensory tests were performed on panellists with tested aspect criteriaabout models and colour harmony. Based on sensory test results, it can be concluded that the modeland colour harmony in